Multifunctional and Mechanically Robust Porous Diamond with Large Electroactive Surfaces via Electrically Conductive and Insulating Templates for 3D Electrode Applications (Adv. Mater. Interfaces 15/2022). Issue 15 (23rd May 2022) - Ashcheulov, Petr; Hák, Ondřej; Sedláková, Silvia; Taylor, Andrew; Baluchová, Simona; Schwarzová‐Pecková, Karolina; Davydova, Marina; Kopeček, Jaromír; Klimša, Ladislav; Vondráček, Martin; Honolka, Jan; Mortet, Vincent
Abstract : Porous Diamond with Large Electroactive Surfaces In article number 2200375, Petr Ashcheulov, Ondřej Hák, and co‐workers demonstrate fabrication of diamond with porous structure. Porous diamond enables effective electrochemical treatment of water pollutants and sensing of biomolecules. The reported strategy allows for manufacturing of porous diamond over large areas, which is of interest for many applications.